Metabolic Response to Tick-Borne Encephalitis Virus Infection and Bacterial Co-Infections - Marta Dobrzyńska; Anna Moniuszko-Malinowska; Iwona Jarocka-Karpowicz; Piotr Czupryna; Monika Groth; Elżbieta Skrzydlewska (Pathogens, 2022)
Ticks are vectors of various pathogens, including tick-borne encephalitis virus and bacteria such as B. burgdorferi and A. phagocytophilum, causing infections/co-infections, which are still a diagnostic and therapeutic problem. Therefore, the aim of this study was to compare the effects of TBEV infection/bacterial co-infection on metabolic changes in the blood of patients before and after treatment. It was found that those infections promote plasma ROS enhanced generation and antioxidant defence reduction, especially in relation to glutathione and thioredoxin systems, despite the increased effectiveness of Nrf2 transcription factor in granulocytes. Observed oxidative stress promotes the oxidative modifications of phospholipids containing polyunsaturated fatty acids (LA, AA, EPA) with increased lipid peroxidation (estimated as 8-isoPGF2α, 4-HNE). It is accompanied by protein modifications measured as 4-HNE-protein adducts, carbonyl groups, dityrosine increase, and tryptophan level decrease, which promote structural and functional modification of the following transcription factors: Nrf2 and NFkB inhibitors. The lower level of 8-iso-PGF2α in co-infections indicates an impairment of the body’s ability to intensify inflammation and fight co-infections, while an increased level of Trx after therapy may contribute to the intensification of the inflammatory process. The obtained results indicate the potential possibility of using the assessed metabolic parameters to introduce targeted pharmacotherapy in cases of TBEV infections/bacterial co-infections.